2020
DOI: 10.1186/s12883-019-1594-x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factor analysis for progressive spinal deformity after resection of intracanal tumors─ a retrospective study of 272 cases

Abstract: Background: Progressive spinal deformity has become a well-recognized complication of intracanal tumors resection. However, the factors affecting post-operative spinal stability remain to be further research. Here, we described the current largest series of risk factors analysis for progressive spinal deformity following resection of intracanal tumors. Methods: We retrospectively analyzed the medical records of the patients with resection of intracanal tumors between January 2009 and December 2018. All patient… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…The advantages of UBE include less damage to the paraspinal musculature, smaller wounds, and better surgical vision. ( 23 , 24 ) The major challenges in UBE are establishing suitable saline irrigation, minimizing complications, and properly localizing the surgical region ( 25 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of UBE include less damage to the paraspinal musculature, smaller wounds, and better surgical vision. ( 23 , 24 ) The major challenges in UBE are establishing suitable saline irrigation, minimizing complications, and properly localizing the surgical region ( 25 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Management after resection will involve close clinical and radiologic follow-up and continued bracing, as the authors have concern for the long-term development of a progressive deformity. A recent retrospective review of 272 cases of intracanal tumor resection found the incidence of postoperative progressive spinal deformity to be 15.8% [ 21 ]. This occurred mostly in patients who had younger age (≤18 years) or tumors that involved multiple segments and preoperative spinal deformity.…”
Section: Discussionmentioning
confidence: 99%
“…Lenke et al reported that the incidence of EP events was 27.0% in 147 cases of severe spinal deformity, while the incidence of neurological complications was 6.1% [ 13 ]. Several surgical factors are involved in the neurological complications that may arise from spinal surgery, including compression and traction of neural structures, osteotomy related injuries, hypotension, and spinal cord ischemia [ 5 7 , 14 , 15 ]. In total, 58 of 177 patients (32.8%) had EP events during the operation.…”
Section: Discussionmentioning
confidence: 99%